Repeated-sprint running in hypoxia alters cognitive function in team-sport athletes - Morrison, J.; Macdonald, I.; Minahan, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Repeated-sprint training in hypoxia (RSH) further improves repeated-sprint ability compared with training in normoxia (RSN; Faiss et al. 2013). Although these findings suggest that RSH is valuable for team-sport athletes, further research is required to ensure that there are no undesirable effects associated with RSH. For example, Li et al. (2000) demonstrated that 1 h of passive exposure to altitude can impact cognitive function which may predispose athletes to reduced neuromuscular control and risk of injury (Swanik et al. 2007). The purpose of this study was to determine the effects of RSH on cognitive performance in team-sport athletes. Methods: Male team-sport athletes (n=12, 24 (5) yr) performed a computer-based cognitive test battery assessing choice reaction time (identification task; IDN) and spatial memory (one card learning task; OCL) before and after repeated-sprint running (4 sets x 4, 4-s sprints; i.e., RSR444). Subjects performed the RSR444 on a non-motorized treadmill in normobaric normoxia (20.9%O2) and hypoxia (14.5%O2). Results: Peak speed and distance achieved during Set 1 and Set 2 of the RSR444 were not different between conditions (p>0.05). However, both peak speed and distance achieved during Set 3 and Set 4 were lower in hypoxia compared with normoxia (p<0.05). Mean SpO2 was 94.5(1.8)% in normoxia and 79.4 (4.0)% in hypoxia after the RSR444. There were no differences in the mean reaction time (RT) for the IDN (p=0.34) or the OCL accuracy score (p=0.49) before the RSR444 between the two conditions. After the RSR444, no changes were observed in RT for the IDN in either normoxia (p=0.55) or hypoxia (p=0.18). The OCL accuracy score did not change after the RSR444 in normoxia (p=0.54) but accuracy was lower after the RSR444 in hypoxia (p=0.03). Discussion: The findings of the present study demonstrate that simple cognitive tasks (i.e., IDN) are not affected by repeated-sprint running in either normoxic or hypoxic environments. In contrast, repeated-sprint running decreases performance of complex cognitive tasks (i.e., OCL accuracy) when performed in hypoxia but not normoxia. Given the negative relationship between cognitive function and noncontact lower-limb injury in athletes (Swanik et al. 2007) coaches should be considerate of the effects of hypoxia on cognitive function when prescribing RSH.